Individualization of footwear for optimizing running economy: A theoretical framework - Connick, M. J.; Lichtwark, G. A. (Journal of Applied Biomechanics, 2025)
Advanced footwear technologies contain thicker, lightweight, and more resilient midsoles and are associated with improved running economy (RE) compared with traditional footwear. This effect is highly variable with some individuals gaining a greater RE benefit, indicating that biomechanics plays a mediating role with respect to the total effect. Indeed, the energy generated by contractile elements and the elastic energy recovered from stretched tendons and ligaments in the legs and feet are likely to change with footwear. Therefore, if RE is to be maximized according to individual characteristics, an individualized approach to footwear selection is required. However, current theoretical frameworks hinder this approach. Here, we introduce a framework that describes causal relationships between footwear properties, biomechanics, and RE. The framework proposes that RE changes with footwear due to (1) a direct effect of footwear properties—for example, increased or decreased energy return—and (2) a mediating effect of footwear on ankle and foot biomechanics and the spring-mass system. By describing the total effect as 2 complementary pathways, the framework facilitates research that aims to separately quantify direct and mediating effects of footwear. This may permit the development of footwear materials that can separately target the direct and individual mediating effects.